Creative Constraints Translation and Authorship - Wilson, Rita; Gerber, Leah (Linguistics, 2012)
This volume addresses one of the central issues in literary translation: the relationship between the creative freedom of the translator and the multiplicity of constraints to which translation is necessarily subject. The links between an author's translation work and his or her own writing are likewise explored. Through a series of compelling case studies, this volume illustrates the parallel and overlapping discourses within the cognate areas of literary studies, creative writing and translation studies, which together propose a view of translation as (a form of) creative writing, and creative writing itself as being shaped by translation processes. The translations of selected contemporary French, Spanish and German texts offer readers some insights into how the translator's work mirrors and complements that of the creative writer. The combination of theory and practice presented in this volume will appeal not just to specialists in translation studies but also to a wider public.